Investigating a firn aquifer near Helheim Glacier (South‐Eastern Greenland) with magnetic resonance soundings and ground‐penetrating radar. Issue 4 (27th July 2018) - Legchenko, Anatoly; Miège, Clément; Koenig, Lora S.; Forster, Richard R.; Miller, Olivia; Solomon, Douglas Kip; Schmerr, Nicholas; Montgomery, Lynn; Ligtenberg, Stefan; Brucker, Ludovic
ABSTRACT: We apply the magnetic resonance sounding (MRS) method to investigate a firn aquifer in the south‐east region of the Greenland ice sheet. Our study aims to delineate and estimate the volume of the recently discovered water stored within the firn (compacted snow) that remains liquid throughout the year. We develop and test successfully a methodology for joint use of MRS and ground‐penetrating radar (GPR). This non‐invasive geophysical approach is particularly well‐adapted to glacier conditions and has a promising future for in situ investigation of water distribution in glaciers. At our field site, MRS showed an aquifer located at variable depths between 20 and 30 m beneath the ice‐sheet surface. At the monitoring site, both MRS and GPR show an increase in the water volume stored between April 2015 and July 2016. MRS estimates suggest that the volume increased by approximately 28%.